TRANSACT: A Transactional Framework for Programming Wireless Sensor/Actor Networks - Demirbas, Murat; Soysal, Onur; Hussain, Muzammil (Information Processing in Sensor Networks; Proceedings: International Conference on Information Processing in Sensor Networks, 2008: St. Louis, MO, 2008)
Effectively managing concurrent execution is one of the biggest challenges for future wireless sensor/actor networks (WSANs): For safety reasons concurrency needs to be tamed to prevent unintentional nondeterministic executions, on the other hand, for real-time guarantees concurrency needs to be boosted to achieve timeliness. We propose a transactional, optimistic concurrency control framework for WSANs that enables understanding of a system execution as a single thread of control, while permitting the deployment of actual execution over multiple threads distributed onseveral nodes. By exploiting the atomicity and broadcast propertiesof singlehop wireless communication, we provide a lightweightimplementation of our transactional framework on the motes platform.